ANTIHYPERGLYCEMIC TEST OF ETHANOL EXSTRACT OF DURIAN (Durio zibethinus Murr.) PEEL AGAINTS MALE MICE (Mus Musculus) - Hamsiana -; Rudi Kartika; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2015)
Diabetes mellitus (DM) is a metabolic disorder and characterized by hyperglycemic circumstances. Hyperglycemic is a condition where the glucose levels ini the blood increased dramatically. One of the pharmacological therapy ia to use ofdrugs that can reduse glucose levels in the blood. Phytochemical test and antihyperglicemic activity from durian (Durio zibethunus Murr.) peel have been carried out. Durio zibethinus Murr. peel was macerated with ethanol 96% then concentrated with rotary evaporators. It obtained rendemen 13.33% . Based on the test result of phytochemistry of secondary metabolites compounds from durian peel showed that etahanol extract containing flavonoid, alkaloid, fenolik, triterpenoid and saponin. Antihyperglicemic activity test use animal test male mice that is injected aloksan. Measurement of blood sugar levels using glucometer and glucose test strip. From antihyperglicemic test it showed that the effectiveness of blood sugar level doses of 36 mg/kg BW from the